Mapping of Electrical Distribution Networks at Jampit Distribution Substations Using ArcGIS - Agung Herdianto; Adi Mustika; Harjo Utomo (LPPM Politeknik Aceh Selatan, 2022)
In the Ijen sub-district, care must be taken to avoid overlapping uses of PTPN XII-owned plantations, resident fields, and the medium-voltage power distribution network. To lessen the interference factor in the distribution of electricity, the proper power distribution path must be chosen. The contact between trees and lightning is one of the variables that disturbs the distribution pathway. It is well known that the Jampit distribution substation in the Ijen district is situated in a region with plantations and private fields, making it susceptible to lightning and contact with trees. The position of distribution substations, medium-voltage overhead lines, and the location of energy users are among the issues examined in this study. In order to create a map of the electricity distribution network at Jampit distribution substations that pass through agricultural land and plantation areas, ArcGIS is used to help process spatial data including regional administration data, type of conductor, power capacity, distribution substation poles and electricity users.